INVESTING IN GIRLS FUTURE: AN ANALYSIS OF LEVEL OF AWARENESS OF SUKANYA SAMRIDDHI YOJANA SCHEME - Haridas, Haritha; P. Saritha Kumari; M Josephin Rangith (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A government-backed savings program called Sukanya Samriddhi Yojana (SSY) aims to improve the financial stability of Indian female children. Using an Analysis of Variance (ANOVA), this study investigates the association between income levels and awareness of the Sukanya Samriddhi Yojana. 150 investors living in the Alappuzha District provided the data. To determine the impact of revenue on the degree of SSY Account awareness, six parameters based on awareness are chosen. Interest rate, tax benefits, withdrawals, account transfers, internet services, and loan facilities are the six parameters that were chosen for this investigation. The results of the ANOVA test showed that income levels had no bearing on awareness levels regarding interest rates and online services, but they did in the cases of tax benefits, withdrawals, and transfers. The research highlights the necessity of focused awareness initiatives to close the knowledge gap and guarantee that everyone may benefit equally from the Sukanya Samriddhi Yojana. Policymakers can improve the scheme's efficacy and reach by tackling these discrepancies, which will ultimately help financially empower female children across all socioeconomic classes.